Evaluación de la competencia lectora de futuros docentes - Felipe Morales, Andrea; Barrios Espinosa, Elvira (Investigaciones Sobre Lectura, 2017)
This paper presents a test aimed at assessing university students’ reading competence –The Reading Competence Test for University Students (in Spanish, Test de Competencia Lectora para Universitarios, Test CLUni)– and the results obtained in the test by prospective Early Years and Primary Education teachers. The theoretical framework underlying the test is followed by description of the pilot stage and the validation process; this included content and expert validity. Next, the test is characterised. It consists of six authentic texts (four continuous and two non-continuous texts) that were selected according to the proposed text types in PISA-2012. Finally, the results obtained in the test by a sample of 288 students in the Bachelor Degree of Early Years (n=148, 51.4%) and Primary Education (n=140, 48,6%) at the University of Málaga in the academic year 2013/4 are presented. Results pertaining the students’ perceptions on the difficulty of the test are also included.